2018
DOI: 10.3390/ijms19113393
|View full text |Cite
|
Sign up to set email alerts
|

High Catalytic Activity of Lipase from Yarrowia lipolytica Immobilized by Microencapsulation

Abstract: Microencapsulation of lipase from Yarrowia lipolytica IMUFRJ 50682 was performed by ionotropic gelation with sodium alginate. Sodium alginate, calcium chloride and chitosan concentrations as well as complexation time were evaluated through experimental designs to increase immobilization yield (IY) and immobilized lipase activity (ImLipA) using p-nitrophenyl laurate as substrate. To adjust both parameters (IY and ImLipA), the desirability function showed that microcapsule formation with 3.1%(w/v) sodium alginat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Cell-free medium, after 24 h fermentation, contained approximately 4700 U/L of extracellular lipase activity. The extracellular lipase extract was used for other studies [19]. At this moment 5.7 g d.w. (dry weigh) cells/L was detected in the culture medium, resulting in, approximately 17 g d.w. of cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-free medium, after 24 h fermentation, contained approximately 4700 U/L of extracellular lipase activity. The extracellular lipase extract was used for other studies [19]. At this moment 5.7 g d.w. (dry weigh) cells/L was detected in the culture medium, resulting in, approximately 17 g d.w. of cells.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the immobilization is a technique which consists to the attachment of enzymes to solid support materials in order to improve their activity, stability and reusability for a continuous process [12]. Several studies reported the different lipases immobilization techniques such as physical adsorption [13], entrapment or microencapsulation [14,15] and covalence binding to a solid matrix [16]. Among these techniques, adsorption may have the highest interest due to its relatively low cost and simplicity [17].…”
Section: Introductionmentioning
confidence: 99%
“…A disadvantage of this support is that small proteins may leach into the bulk medium. For example, a crude extract containing lipases of Yarrowia lipolytica was immobilized by microencapsulation in alginate [100]. The immobilization itself was successful, with the immobilized biocatalyst initially having high hydrolytic activity against p-nitrophenyl laurate; however, 50% of the activity had leached out of the alginate beads by the end of the reaction [100].…”
Section: Alginatementioning
confidence: 99%
“…For example, a crude extract containing lipases of Yarrowia lipolytica was immobilized by microencapsulation in alginate [100]. The immobilization itself was successful, with the immobilized biocatalyst initially having high hydrolytic activity against p-nitrophenyl laurate; however, 50% of the activity had leached out of the alginate beads by the end of the reaction [100]. The optimization of immobilization parameters can reduce the leaching of small proteins, for example, by controlling the amount of alginate and the concentration of Ca 2+ to fine tune the gel properties [101].…”
Section: Alginatementioning
confidence: 99%